Changes in Occurrence of Diarrheal and Respiratory Diseases before and during COVID-19 Pandemic among Nepalese Population: A cross-sectional Study - Kaphle, Maheshor; Paudel, Anil; Adhikari, Laxmi; Shrestha, Pratibha; Khadka, Santosh; Karki, Rajesh (Journal of Karnali Academy of Health Sciences, 2023)
Background: The government of Nepal has adopted several preventive and control measures to control spread of coronavirus disease(COVID-19). This study is aimed to determine whether the use of preventive and control measures like hand washing, social distancing, lockdown, and mask-wearing have significantly slowed down the spread of infectious diseases like diarrhoea and respiratory illnesses during the pandemic period.Methods: A descriptive and cross-sectional study was conducted among 3086 participants across Nepal via electronic media from 28-July to 30-August, 2020. The participants were asked about their experiences with diarrhoea and respiratory symptoms in the three months before and during the COVID-19 pandemic. The Mc-Nemar test was used to compare the incidence of respiratory and diarrheal diseases before and during the pandemic period.Results: Compared to before and during the COVID-19 pandemic, vomiting (3.3%), diarrhoea (7.3%) and abdominal pain (12.1%) decreased to 2.8%, 6.9%, and 6.1%, respectively. Before the onset and during the COVID-19 pandemic lockdown, the prevalence of dysentery, stomach pain was statistically different (p-value